2016
DOI: 10.1038/tp.2016.82
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and behaviour imaging: a novel method to measure mother–infant interaction using video 3D reconstruction

Abstract: Studying early interaction is essential for understanding development and psychopathology. Automatic computational methods offer the possibility to analyse social signals and behaviours of several partners simultaneously and dynamically. Here, 20 dyads of mothers and their 13–36-month-old infants were videotaped during mother–infant interaction including 10 extremely high-risk and 10 low-risk dyads using two-dimensional (2D) and three-dimensional (3D) sensors. From 2D+3D data and 3D space reconstruction, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 34 publications
(25 reference statements)
4
21
2
Order By: Relevance
“…In fact, Hammal et al ( 2015a ) suggest a continuum with increasing levels of motion activity going from depressed, to neutral, to positive and finally negative affect. The previous studies, excepting the results from Leclère et al ( 2016 ), also suggest that higher levels of movement coordination, i.e., where the partners adjust their level of motion activity to each other, are associated with non-conflictual periods and a better rating of the relationship. In mother-infant interaction, when the mother coordinates her movements to her infant's, she shows the infant that she is aware of him and that she would like to participate in his experience (Stern, 2004 ).…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…In fact, Hammal et al ( 2015a ) suggest a continuum with increasing levels of motion activity going from depressed, to neutral, to positive and finally negative affect. The previous studies, excepting the results from Leclère et al ( 2016 ), also suggest that higher levels of movement coordination, i.e., where the partners adjust their level of motion activity to each other, are associated with non-conflictual periods and a better rating of the relationship. In mother-infant interaction, when the mother coordinates her movements to her infant's, she shows the infant that she is aware of him and that she would like to participate in his experience (Stern, 2004 ).…”
Section: Introductionmentioning
confidence: 86%
“…For example, Væver et al ( 2013 ) reported that the variability in head distance between mothers and infants was lower for mothers with postpartum depression than for non-clinical mothers. In another study, Leclère et al ( 2016 ) showed that it was possible to discriminate between non-clinical mothers and mothers who were emotionally neglecting, based on motion features such as motion activity, pause, and overlapping motion. Finally, Delaherche et al ( 2013 ) demonstrated that it was possible to discriminate between autistic and non-clinical children interacting with therapists using motion features such as gestural and pause durations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This synchrony phenomena remains true accross modalities and behaviors whether focusing on speech turns (e.g. Weisman et al, 2015;Jaffe et al, 2001), motion (Leclère et al, 2016), head movements (e.g. Hammal et al, 2015) and smile (Messinger et al, 2008).…”
Section: Synchrony and The Role Of Oxt During Early Interactionmentioning
confidence: 96%